PENGARUH PENGAWASAN KERJA, KOMITMEN KARYAWAN DAN KOMUNIKASI TERHADAP PRESTASI KERJA KARYAWAN PADA PT. BPR PIJER PODI KEKELENGAN SIMPANG POS MEDAN - Lumbanbatu, Jhon David; Sinaga, Ria Veronica; Sembiring, Sabeth (Jurnal Manajemen dan Bisnis, 2021)
This study aims to examine and analyze the effect of Work Supervision, Employee Commitment and Communication on Employee Performance at PT. BPR Pijer Podi Kekelengan Medan Post Intersection. The sampling technique used is saturated sampling method and the analysis method used is multiple linear regression. From the research results, the multiple regression equation is as follows: PKK = 1.059+ 0.287PK + 0.309KK + 0.135K + ei. This means that the Employee Commitment (KK) variable has a greater influence on employee work performance, because the regression coefficient is greater, namely 0.309. The results of the t test show that the employee commitment variable has a positive and significant effect on employee work performance where the t value (4.233)> the t table value (1.682) and the significant value 0.000 <Î± (0.05). Work supervision has a positive and significant effect on employee work performance, it can be seen from the t value (3,419) <t table value (1.682) and the significant value 0.001 <Î± (0.05). Communication has a positive and significant effect on employee performance. This can be seen from the t value (1.238)> the t table value (1.682) and the significant value 0.012 <Î± (0.05). The results of the F test show that work supervision, employee commitment and communication have a positive and significant effect on employee performance (Fcount of 44.5213> F table of 2.59). R Square is 0.761 or 76.1% means that variations in employee work performance can be explained by job supervision, employee commitment and communication by 76.1% and the remaining 23.9% can be explained by other variables not included in this study such as work environment, work motivation, morale and work discipline etc. From the research and discussion, it is better if PT. BPR Pijer Podi Kekelengan Simpang Pos Medan is increasingly improving employee work performance through employee commitment such as fostering a sense of employee psychological ties to the organization including work involvement, loyalty, and feelings of trust in the values and goals of the company and involving employees in decision making. And the establishment of a good communication process as well as providing encouragement and good and appropriate work supervision for employees so that they remain enthusiastic in carrying out their duties.